Vitamin D, exercise, and immune health in athletes: A narrative review - Crescioli, Clara (Frontiers in Immunology, 2022)
Vitamin D exerts important extra-skeletal effects, exhibiting an exquisite immune regulatory ability, affecting both innate and adaptive immune responses through the modulation of immunocyte function and signaling. Remarkably, the immune function of working skeletal muscle, which is fully recognized to behave as a secretory organ with immune capacity, is under the tight control of vitamin D as well. Vitamin D status, meaning hormone sufficiency or insufficiency, can push toward strengthening/stabilization or decline of immune surveillance, with important consequences for health. This aspect is particularly relevant when considering the athletic population: while exercising is, nowadays, the recommended approach to maintain health and counteract inflammatory processes, “too much” exercise, often experienced by athletes, can increase inflammation, decrease immune surveillance, and expose them to a higher risk of diseases. When overexercise intersects with hypovitaminosis D, the overall effects on the immune system might converge into immune depression and higher vulnerability to diseases. This paper aims to provide an overview of how vitamin D shapes human immune responses, acting on the immune system and skeletal muscle cells; some aspects of exercise-related immune modifications are addressed, focusing on athletes. The crossroad where vitamin D and exercise meet can profile whole-body immune response and health.